Use of pregnant mare’s sera gonadotropin (PMSG) in media in vitro maturation of cow oocytes - Zaituni Udin; Jaswandi .; Tinda Afriani; Leonardo E (Jurnal Ilmu Ternak dan Veteriner, 2007)
It is known that hormone addition in media helps in vitro maturation of oocyte. This research was aimmed to determine the effect of PMSG in media to maturation rate and nucleous developvement of cow oocyte. Ovaries were obtainned from local slaughterhouse. The media used for in vitro maturation of oocyte was TCM- 199 and the treatment was 3 levels of PMSG: 0, 10 and 20 mg/ml. Result of this research showed that the dose of PMSG in maturation media was significantly affected (P<0.05)  nucleolus development of oocytes and maturation rate. The average of germinal vesicle (GV) stage in 3 levels of PMSG 0, 10 and 20 mg/ml were 38.33; 12.64 and 9.64%, respectivelly. There was no germinal vesicle breakdown (GVBD) found in 3 levels of PMSG addition. The nucleous development of metaphase–I (M-I) were 7.64; 20.2 and 22.00%, but the average of maturation rate (M-II)  was 16.32; 48.10 and 35.34% for 3 levels of PMSG: 0, 10 and 20 mg/ml, respectivelly. It is concluded that 10 mg/ml PMSG in media of in vitro maturation resuls in the highest maturation rate of cow oocyte. Key Words: Oocyte, Maturation, In vitro, Hormone, PMSG